2007
DOI: 10.1111/j.1600-6143.2006.01655.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Islet Oxygen Consumption Rate and DNA Measurements Predict Diabetes Reversal in Nude Mice

Abstract: There is a need for simple, quantitative and prospective assays for islet quality assessment that are predictive of islet transplantation outcome. The current state-of-the-art athymic nude mouse bioassay is costly, technically challenging and retrospective. In this study, we report on the ability of 2 parameters characterizing human islet quality: (1) oxygen consumption rate (OCR), a measure of viable volume; and (2) OCR/DNA, a measure of fractional viability, to predict diabetes reversal in nude mice. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
162
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(174 citation statements)
references
References 22 publications
6
162
6
Order By: Relevance
“…In a retrospective analysis of type 1 diabetic islet graft recipients, a weak correlation was seen between the number of duct cells injected and the acute insulin secretory response at post-transplant year 2, but this was not further examined against other variables [42]. Only a subgroup of free graft recipients (4/12) exhibited a metabolic correction, as in other animal studies with human islet cell grafts [43][44][45]. The effect was not achieved within the first week, probably reflecting the time needed to vascularise implants in an extravascular space [46], and probably not facilitated in compact subcapsular implants.…”
Section: Discussionmentioning
confidence: 98%
“…In a retrospective analysis of type 1 diabetic islet graft recipients, a weak correlation was seen between the number of duct cells injected and the acute insulin secretory response at post-transplant year 2, but this was not further examined against other variables [42]. Only a subgroup of free graft recipients (4/12) exhibited a metabolic correction, as in other animal studies with human islet cell grafts [43][44][45]. The effect was not achieved within the first week, probably reflecting the time needed to vascularise implants in an extravascular space [46], and probably not facilitated in compact subcapsular implants.…”
Section: Discussionmentioning
confidence: 98%
“…It has been repeatedly shown that native pancreatic islets have a disproportionately high level of vascularization (13)(14)(15)(16)(17)(18). During the process of islet isolation their vasculature is disrupted, and after transplantation the islets depend on oxygen diffusion from tissue surrounding the transplantation site until revascularization has occurred.…”
Section: Discussionmentioning
confidence: 99%
“…This assay is especially well suited to encapsulated islets and was proven to be directly correlated to islet performance in vivo. According to several other groups, this assay is well established and verified as an excellent predictor of transplantation outcomes (58,59). …”
Section: Discussionmentioning
confidence: 99%